RANCANG BANGUN SISTEM KONTROL SUHU PADA PERANGKAT SMART GREENHOUSE UNTUK TANAMAN PURING DENGAN FUZZY LOGIC METODE MAMDANI - Mochammad Habib Anshory; Muhammad Aziz Muslim; Goegoes Dwi Nusantoro (Jurnal Mahasiswa TEUB, 2023)
When Covid 19 Pandemic, Ornamental plant cultivation is one of favourite sector, thus the farmer of ornamental plant received so many demands cannot fulfil that. Beside of that, there are some kinds of ornamental plant which is hard to be treated. Croton is an ornamental plant which is hard to be treated, but become so famous in Indonesia recently. So a tool that can facilitate the plant is needed to make the plant grown optimally. The research started with designing the smart greenhouse’s design, then designing the hardware and software of the smart greenhouse. After the design is finished, smart greenhouse can be tested with the desired parameter. After it work properly, then carry out the sample data to analyse with the fuzzy logic mamdani method with 28°C as setpoint.Based on the test during the day, System has the output that is able to control the temperature, but it does not match with the setpoint that have been set. Beside of that, system take a long time to reach the steady state condition, which is 45 minutes and 42 seconds. But during the night, system can not work properly because there is no heating actuator in this system Keywords: Temperature, Smart Greenhouse, Fuzzy Logic, Croton